2012
DOI: 10.1177/1477153512461372
|View full text |Cite
|
Sign up to set email alerts
|

Electric lighting at the workplace in offices: Efficiency improvement margins of automation systems

Abstract: Electric lighting is one of the major energy loads in non-residential buildings. It is strategic to examine the real behaviour of available lighting control systems for practical applications so as to allow the development of strategies that can improve the reliability of measured data (in terms of illuminance at the desktop) and the consequent response of the control system. This paper presents a case study of an office where lighting data measured at the desktop and read by the automation system have been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Even in a shallow perimeter office space, illuminance on the workplane can vary by a factor of ten or more [60]. For practical reasons, illuminance sensors are often positioned on the ceiling [61] or on the window frame measuring vertical illuminance on the view portion of the window surface [62]. However, research on occupants' visual comfort, and lighting and blinds use behaviour has been mostly focused on workplane conditions [22].…”
Section: Control For Visual Comfortmentioning
confidence: 99%
“…Even in a shallow perimeter office space, illuminance on the workplane can vary by a factor of ten or more [60]. For practical reasons, illuminance sensors are often positioned on the ceiling [61] or on the window frame measuring vertical illuminance on the view portion of the window surface [62]. However, research on occupants' visual comfort, and lighting and blinds use behaviour has been mostly focused on workplane conditions [22].…”
Section: Control For Visual Comfortmentioning
confidence: 99%
“…Another study compared the illuminance measured by ceiling-mounted sensors with illuminance meters placed on desks, and found a difference of up to 350 lux and 1000 lux on a typical spring and summer day respectively (Chiogna, Albatici and Frattari, 2013). They concluded that by adjusting the ceiling sensor value with correction functions, can yield an energy savings of up to 10%, by reducing the unnecessary use times for electric lighting.…”
Section: Sensors Detecting Light Levelsmentioning
confidence: 99%
“…In the first six years of Reading University’s carbon management programme which started in 2009, lighting retrofit projects made up 12% of the total carbon energy efficiency projects and the nine lighting upgrades cost a total of £810,532 and achieved savings of £164,951 per annum and 800 tCO 2 e. Lighting incurs a significant financial and carbon cost: although engineering standards for lighting specifications and codes of practice detail optimum and quality lighting solutions 1 there is little attention paid to how these lighting systems perform in practice. 2 While the Chartered Institution of Building Services Engineers (CIBSE) guidance suggests training should be given in the use of lighting controls, the theoretical and practical impact of training 4000 staff and invited public speakers indicates that intuitive lighting controls are essential in all university spaces and could negate the need for training if designed properly. Although this issue is most salient for higher education institutions dealing with a large annual turnover of staff and students, it clearly also arises for any large organisation, in particular ones in the public sector where large numbers of visitors are interacting with lighting and, potentially, lighting controls.…”
Section: Introductionmentioning
confidence: 99%